HUBUNGAN ANTARA PENGETAHUAN TERHADAP MAKANAN GIZI SEIMBANG DENGAN KESEHATAN KULIT WAJAH PADA MAHASISWA S1 PENDIDIKAN TATA RIAS - Lailia Safira Zahra; Nieke Andina Wijaya; Sri Usodoningtyas; Novia Restu Windayani (Program Studi Pendidikan Tata Rias, 2026)
Knowledge is an important factor in determining the actions or practices a person will carry out. Individuals who have good knowledge of a balanced nutritious diet tend to develop more positive attitudes and are more likely to apply balanced eating patterns in their daily lives. This consistent application of balanced nutrition can influence overall health, including facial skin health, because adequate nutrient intake helps support skin regeneration, maintain hydration, and improve the skin’s ability to repair and protect itself. This study aimed to examine the relationship between knowledge of balanced nutrition and facial skin health among undergraduate students in the Makeup Education (S1 Pendidikan Tata Rias) program. The research employed a quantitative design with a total of 50 respondents. Data were collected using two instruments: a test to measure respondents’ knowledge of balanced nutrition and a questionnaire to assess facial skin health. The relationship between the two variables was analyzed using the chi-square test. The results indicated a significant association between knowledge of balanced nutrition and facial skin health among the students. The analysis produced a chi-square value of 52.417 with a p-value of 0.029 (p < 0.05), suggesting that the variables are statistically related. Therefore, the study concludes that there is a significant relationship between balanced-nutrition knowledge and facial skin health in undergraduate Makeup Education students.Keywords: knowledge, balanced nutritional food, facial skin health